Tafsir Alquran Kontemporer: Kajian atas Tafsir Tematik-Kontekstual Ziauddin Sardar - Taufan Anggoro (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Ziauddin Sardar is a Muslim thinker who interprets the Koran in a thematic-contextual, with a very critical presentation. Sardars interpretation is contained in one of his works entitled Reading the Quran: The Contemporary Relevance of the Sacred Text of Islam. This article aims to examine the thoughts of Sardar in terms of interpreting the Quran. The extent to which the methodology used by Sardar in interpreting the Quran. By using descriptive-analytical methods and hermeneutical-analysis techniques, Sardars interpretation is examined to what extent hermeneutic operational forms appear within them. It also examined how the influences of other figures in shaping Sardars interpretation. The results of this study show that Sardars contextual interpretation reveals forms of hermeneutic surgery. Where more aiming aspects of the context and contextualization of the Quran. Then methodologically, Sardars interpretation was influenced by Rahmans double movement theory, and Saeeds legal ethico theory. Then the style of Hermeneutics of Liberation Farid Esack was strongly felt in the contextualization of the Koran by Sardar. Sardars efforts are not limited to explaining the meaning of the Quran, but digging into the substance of the text that is manifested in the form of al-Qurans social criticism of various religious phenomena today.